Adaptation, acceptability and feasibility of a Short Food Survey to assess the dietary intake of children during attendance at childcare. Issue 9 (17th June 2020) - Grady, Alice; Fielding, Alison; Golley, Rebecca K; Finch, Meghan; Hendrie, Gilly A; Burrows, Tracy; Seward, Kirsty; Lecathelinais, Christophe; Yoong, Sze Lin
Abstract: Objective: To (i) describe the adaptation of the Short Food Survey (SFS) for assessing the dietary intake of children (2–5 years) during attendance at Early Childhood Education and Care (SFS-ECEC); (ii) determine the acceptability and feasibility of the SFS-ECEC; and (iii) compare the SFS-ECEC to direct observations for assessing dietary intake of children in care. Design: The adapted forty-seven-item SFS-ECEC was completed by childcare educators to capture individual child's usual intake over the past month. Acceptability and feasibility were assessed via educator self-report and completion rates. Mean servings of food groups consumed in accordance with dietary guidelines reported in the SFS-ECEC were compared to those obtained by a single-day direct observation via visual estimation conducted by trained personnel. Mean differences, intra-class correlations, Bland–Altman plots, percentage agreement and Cohen's κ were examined. Setting: Early Childhood Education and Care, NSW, Australia. Participants: Educators and children. Results: 213 (98·61 %) SFS-ECECs were returned. Acceptability was high with 86·54 % of educators reporting the tool as easy to understand. Mean differences in servings of food groups between the SFS-ECEC and direct observation were statistically significantly different for five out of six foods and ranged 0·08–1·07, with intra-class correlations ranging 0·00–0·21. Agreement between the methods in the classification of children meeting or not meeting dietary guidelines ranged 42·78–93·01 %, with Cohen's κ ranging −0·03 to 0·14. Conclusions: The SFS-ECEC is acceptable and feasible for completion by childcare educators. While tool refinement and further validation is warranted, small mean differences suggest the tool may be useful in estimating group-level intakes.